2000
DOI: 10.1039/b006988o
|View full text |Cite
|
Sign up to set email alerts
|

Direct biocatalytic synthesis of functionalized catechols: a green alternative to traditional methods with high effective mass yield

Abstract: Several catechols have been prepared directly from aromatic precursors by treatment with the recombinant organism Escherichia coli JM109 (pDTG602), which expresses both toluene dioxygenase (TDO) and dihydrocatechol dehydrogenase (DHCD), the first two enzymes in the natural biodegradation pathway of aromatics by Pseudomonas species. The yields and the ease of preparation of these compounds are compared with traditional chemical methods. For three of the products, the E value and EMY (effective mass yield, is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Substituted catechols, especially 3-substituted catechols, are useful precursors for making pharmaceuticals (14); one of these compounds, 3-methoxycatechol, is an important intermediate for the antivascular agents combretastatin A-1 and combretastatin B-1 (5). Methoxyhydroquinone is used in the synthesis of triptycene quinones that have been shown to have anti-leukemia cell activity (16), and methylhydroquinone has been recently reported to be used in the synthesis of (Ϯ)-helibisabonol A and puraquinonic acid, which are precursors of agrochemical herbicides and antileukemia drugs, respectively (15,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Substituted catechols, especially 3-substituted catechols, are useful precursors for making pharmaceuticals (14); one of these compounds, 3-methoxycatechol, is an important intermediate for the antivascular agents combretastatin A-1 and combretastatin B-1 (5). Methoxyhydroquinone is used in the synthesis of triptycene quinones that have been shown to have anti-leukemia cell activity (16), and methylhydroquinone has been recently reported to be used in the synthesis of (Ϯ)-helibisabonol A and puraquinonic acid, which are precursors of agrochemical herbicides and antileukemia drugs, respectively (15,20).…”
mentioning
confidence: 99%
“…Canada et al (6) used DNA shuffling to evolve toluene ortho-monooxygenase (TOM) from Burkholderia cepacia G4 for 1-naphthol synthesis, and one mutant (TomA3 V106A) with sixfold-increased activity was found. Furthermore, substituted catechols (e.g., 3-bromocatechol, 3-methoxycatechol, 3-iodocatechol, and 3-methylcatechol) were synthesized from substituted benzenes in two steps by using recombinant Escherichia coli expressing both toluene dioxygenase and dihydrocatechol dehydrogenase (5).…”
mentioning
confidence: 99%
“…Diagnostic criteria of cyclic voltammetry, the consumption of two electrons per molecule of 1a, and the spectroscopic data (IR, 1 H-NMR, 13 C-NMR and MS) of the isolated product, indicated that the reaction mechanism of electrooxidation of 1a in the presence of phenyl-Meldrum's acid (3) is EC (electrochemical and chemical reactions) mechanism 15) (Chart 1).…”
Section: Resultsmentioning
confidence: 99%
“…The precipitated solid was collected by filtration and washed several times with water. After washing, products were characterized by IR, 1 H-NMR, 13 C-NMR, and MS. The isolated yields after washing are reported.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation